Estimação de valores estatísticos de referência para as internações por condições sensíveis a atenção primária em municípios brasileiros - Cavalcanti, Gilmara Alves (2017)
Many indicators have been used to verify the e ciency and quality of services in primary health care. Recently, this level of attention has been evaluated in Brazil. The ambulatory cary sensitive conditions (ACSC), represent a set of health problems that should not reach tertiary care in large numbers, since an e ective primary care action would solve some of these pathologies. Hear, the present study is justi ed by the need to use hospitalizations for ACSC as a base for quality and access indicator for the Primary Care of the health system of Brazilian cities, in association with the Family Health Strategy (FHS). Therefore, we aim to estimate statistical reference values for ambulatory cary sensitive conditions, based on the adjustment of continuous probability distributions, in order to classify the health system of the Brazilian cities into levels of performance, namely: desirable, intermediate, worrying and not acceptable. The thesis that is defended is that the achievement of a statistical reference value, capable of classifying by ASCS, in performance levels for the Brazilian cities, will aid in decision-making processes in the units of FHS, optimizing the health actions in these units, as well as, providing the prevention of unnecessary expenses in the other levels of attention. This is an epidemiological, ecological and inferential study of quantitative approaches, based on the secondary database of the Hospital Information System of the Unique Health System, with the selection of absolute frequencies of diagnostic groups referring to ambulatory cary sensitive conditions to Primary Care, for 2015. Subsequently, these frequencies were transformed into rates per 10,000 inhabitants, making it possible to compare the ACSCs of all Brazilian cities, regardless of their population contingents. From the statistical point of view, the adjustment of continuous probability distributions through the goodness-of- t tests and graphic support were processed using software R, version 3.0.3. Based on the results, a greater incidence of hospital admissions was observed due to pathologies related to gastroenteric, cardiac and renal problems. In view of the three scenarios investigated (Brazil, Northeast and Para ba), the Northeast presents records of hospitalizations for asthma, a diagnosis not observed as one of the three highest incidences at national and state level. It was also evidenced that most of the Brazilian cities investigated in this study have their health systems classi ed as not acceptable. The city of S~ao Paulo, for example, is one such case accounting for 9.471 hospitalizations of patients with heart failure in 2015. Thus, its health system would be considered desirable if there were up to 1.532 records. An intermediate level of performance would range from more than 1.532 to a maximum of 2.944 cases, while the level of concern would be more than 2.944 to 4.177 hospitalizations. An unacceptable performance level is recorded from 4.177 ICSAP. In Brazil, when it comes to the Basic Attention scenario, although advances are perceived, the prospect of reducing the ACSC to minimum values, as is desirable, is still far from the reality. The use of the statistical reference value may constitute a potential tool, ready to use of the administrative managers in order to direct and subsidize proposals of health actions in the cities under their responsibility.